Extraction of anthocyanins from purple corn cobs of Zea mays L. - Gorriti G., Arilmí (2009)
At the present investigation the good conditions for the extraction of anthocyanins from purple corn cobs were investigated, by means of the employment of a complete design at random with factorial arrangement 2A3B4C4D. The factors studied were pH, solvent, time and temperature. The results showed anthocyanins between 8,404 and 47,984 mg/g of cob according to the method of differential pH. Analysis of four factors were presented.